The Effect of Learning Facilities and Family Environment on Motivation to Learn of Prospective Elementary Teacher Education on Online Learning - Eva Astuti Mulyani; Mahmud Alpusari; Elpri Darta Putra (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
This research purpose determines the effect of learning facilities and family environment on motivation to learn of prospective elementary teacher education, Faculty of Teacher Training and Education, Universitas Riau on online learning. The research method used is descriptive quantitative. The data used are primary data obtained directly from filling out a questionnaire by prospective elementary teacher education Class 2018, 2019, and 2020 students totaling 180 students. The results showed that there was a positive and significant effect of learning facilities and family environment on motivation to learn of prospective elementary teacher education in learning during, with the results of testing with the F test that obtained an F value of 21.272 with a significance value of F of 0.000 or a sig F value of <0.05. The multiple regression test results show that the coefficient of determination (R2) is 0.440 or 44%.